Is social mindfulness perceptible and effective? Its associations with personality as judged by others and its impact on patients' satisfaction with their care teams. (February 2023) - Altmann, Tobias; Roth, Marcus
Abstract: Social mindfulness has been described as the socially relevant disposition of being attentive to and considerate of other people's needs and acting accordingly. However, previous studies have not included actual other people. The goal of the present study is to test the hypothesis that people high versus low in social mindfulness are perceived as different by and have different impacts on the people in their personal environments. In our study, we used caregivers as primary participants and two types of other rater. First, primary participants were rated by their private long-term contacts (e.g., closest friend or significant other) on empathy, agreeableness, and honesty/humility. Second, patients provided satisfaction ratings of the care they received from their caregivers (i.e., primary participants). We found small associations between social mindfulness and other-rated empathy but no associations with other-rated agreeableness or honesty/humility. By contrast, the association between caregivers' social mindfulness and patients' satisfaction with their received care was large. The findings are interpreted with regard to differences in levels of acquaintanceship. We speculate that social mindfulness may be more relevant in formal settings than in close relationships.